Accuracy of deformable image registration techniques for alignment of longitudinal cholangiocarcinoma CT images. Issue 4 (12th February 2020) - Sen, Anando; Anderson, Brian M.; Cazoulat, Guillaume; McCulloch, Molly M.; Elganainy, Dalia; McDonald, Brigid A.; He, Yulun; Mohamed, Abdallah S. R.; Elgohari, Baher A.; Zaid, Mohamed; Koay, Eugene J.; Brock, Kristy K.
Abstract : Purpose: Response assessment of radiotherapy for the treatment of intrahepatic cholangiocarcinoma (IHCC) across longitudinal images is challenging due to anatomical changes. Advanced deformable image registration (DIR) techniques are required to correlate corresponding tissues across time. In this study, the accuracy of five commercially available DIR algorithms in four treatment planning systems (TPS) was investigated for the registration of planning images with posttreatment follow‐up images for response assessment or re‐treatment purposes. Methods: Twenty‐nine IHCC patients treated with hypofractionated radiotherapy and with pretreatment and posttreatment contrast‐enhanced computed tomography (CT) images were analyzed. Liver segmentations were semiautomatically generated on all CTs and the posttreatment CT was then registered to the pretreatment CT using five commercially available algorithms (Demons, B‐splines, salient feature‐based, anatomically constrained and finite element‐based) in four TPSs. This was followed by an in‐depth analysis of 10 DIR strategies (plus global and liver‐focused rigid registration) in one of the TPSs. Eight of the strategies were variants of the anatomically constrained DIR while the two were based on a finite element‐based biomechanical registration. The anatomically constrained techniques were combinations of: (a) initializations with the two rigid registrations; (b) two similarity metrics — correlation coefficient (CC) and mutual information (MI); and (c) with and without a controlling region of interest (ROI) ‐ the liver. The finite element‐based techniques were initialized by the two rigid registrations. The accuracy of each registration was evaluated using target registration error (TRE) based on identified vessel bifurcations. The results were statistically analyzed with a one‐way analysis of variance (ANOVA) and pairwise comparison tests. Stratified analysis was conducted on the inter‐TPS data (plus the liver‐focused rigid registration) using treatment volume changes, slice thickness, time between scans, and abnormal lab values as stratifying factors. Results: The complex deformation observed following treatment resulted in average TRE exceeding the image voxel size for all techniques. For the inter‐TPS comparison, the Demons algorithm had the lowest TRE, which was significantly superior to all the other algorithms. The respective mean (standard deviation) TRE (in mm) for the Demons, B‐splines, salient feature‐based, anatomically constrained, and finite element‐based algorithms were 4.6 (2.0), 7.4 (2.7), 7.2 (2.6), 6.3 (2.3), and 7.5 (4.0). In the follow‐up comparison of the anatomically constrained DIR, the strategy with liver‐focused rigid registration initialization, CC as similarity metric and liver as a controlling ROI had the lowest mean TRE — 6.0 (2.0). The maximum TRE for all techniques exceeded 10 mm. Selection of DIR strategy was found to be a statistically significant factor for registration accuracy. Tumor volume change had a significant effect on TRE for finite element‐based registration and B‐splines DIR. Time between scans had a substantial effect on TRE for all registrations but was only significant for liver‐focused rigid, finite element‐based and salient feature‐based DIRs. Conclusions: This study demonstrates the limitations of commercially available DIR techniques in TPSs for alignment of longitudinal images of liver cancer presenting complex anatomical changes including local hypertrophy and fibrosis/necrosis. DIR in this setting should be used with caution and careful evaluation.